Determinants of overhang in affordable housing: a case study of Mukim Sitiawan, Perak - Khairul Aliza, Ahmad Ajadmuqrie (2025)
Affordable housing overhang has become a critical issue in Mukim Sitiawan, Perak, affecting the efficiency of the housing market and the accessibility of homes for lower-income groups and middle-income groups. This research investigates the key determinants of overhang in affordable housing specifically in Mukim Sitiawan, Perak. The research is guided by two research objectives. The first objective is to identify the determinants of overhang in affordable housing and the second objective is to analyse and rank the most determinants of overhang in affordable housing from industrial players perspective which are housing developers and estate agents. Data was collected from secondary sources such as articles, journals and websites to design the interview question. This research uses qualitative method, and semi structured interviews were conducted with three estate agent and two housing developer that selected from purposive sampling. This research found that determinants of overhang affordable housing are location preferences, household income, house design public facilities and neighbourhood surrounding. Based on the interview session, three form five respondents agreed household income is the main determinant of overhang affordable housing in Mukim Sitiawan, Perak. This research contributes valuable insights for policymakers, developers, and investors by highlighting the underlying determinants of overhang and actionable recommendations to mitigate this issue, ultimately enhancing the effectiveness of affordable housing in Mukim Sitiawan, Perak.